Plastyczne Skręcanie Prętów - Mioduchowski, A. (Engineering Transactions, 1971)
In this retrospective paper devoted to the problem of plastic twisting of rods, special stress is laid on the problem connected with the appearance of plastic inhomogeneity and the associated numerical problem. This paper consists of the following six chapters: 1 – elastic twisting of prismatic rods; 2 – carrying boundary (for homogeneous, inhomogeneous and anisotropic rods); 3 – elastic-plastic twisting (for homogeneous and inhomogeneous rods); 4 – certain problems of optimalization of shape and inhomogeneity; 5 – generalizing of problems of plastic twisting of rods: a) – rods of varying diameter and rods of a torous shape, b) – compound loadings: stretching and twisting, buckling and twisting – for homogeneous and inhomogeneous rods; 6 – modelling and experimental results (for homogeneous and inhomogeneous rods).